(untitled) (The Strategic Review for Southern Africa, 2020)
The article assesses the state of oversight of the budget and expenditure of the South African civilian intelligence services (now called the State Security Agency). The roles of various structures, including the National Treasury, the Executive, the Joint Standing Committee on Intelligence (JSCI) and the Auditor-General, during the period 1995 to 2014, are examined. The article argues that whilst the system of financial oversight has strengths, there are systemic weaknesses which have resulted in uneven levels of financial accountability over the years. The article therefore proposes that measures to strengthen the system of oversight are needed to improve financial accountability. These include reforming the relevant legislation and providing more robust powers to the oversight actors.